Exploring Educators’ Viewpoints on Supporting their Pupils’ Mental Health: A Q methodological Study - Pritchard, Isobel (2021)
Evidence of declining mental health among children and young people in the UK has become a focus of increasing socio-political concern (NHS Digital, 2018; Weale, 2019; Newlove-Delgado et al., 2021) . Mental health difficulties in this age group are detrimental to academic success (Deighton et al., 2018) and associated with negative long-term impacts upon adult health, income and marriage stability (Jokela et al., 2009; Goodman et al., 2011). Government publications have consequently sought to promote schools as universal providers of tier one mental health support (DoH & DfE, 2017; DfE, 2018a). However, the success of educational reforms is moderated by their acceptability and feasibility to the frontline staff tasked with implementation (Assor et al., 2009). Stephenson’s (1935) Q methodology was used to explore the holistic viewpoints educators share around their involvement in school-based mental health provision. Twenty-two members of primary and secondary school staff (including teachers, headteachers and teaching assistants), completed an online activity ranking 61 views on this topic in line with their own level of agreement. By-person factor analysis clustered participants with similar patterns of item rankings, facilitating identification of two distinct viewpoints among the group. These were interpreted and named as follows: 1) It’s our duty: Well-positioned, well-equipped and highly motivated 2) Help us to help them: The need for training, capacity and collaboration Qualitative characteristics of these viewpoints were discussed in relation to wider literature and implications for policy and practice. School staff’s divergent levels of confidence in their provision suggested a continued need for more equitable access to quality-assured mental health training, tailored to their role and purposes. External professionals with expertise in child psychology and implementation science could also be further mobilised in supporting educators to identify vulnerable pupils and robustly measure the impact of their work.